Modular test plan for inference on Software Maintenance based on Markov Model - Alam, Mahtab (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
In software industry, the high cost of maintenance of large-scale software put emphasis on the need to manage the maintainability in earlier phases of software system. This paper considers the assessing of the maintenance problem of a software system that can be decomposed into a finite number of modules. It uses a Markov model for transfer of control from one module to another module in order to develop the system for maintainability by detecting and fault module and then repair this module to operate. An operational test procedure is considered in which only the fault modules are maintained and the system is considered reliable if and only if no faults are observed during testing. The minimum number of test required of each module is determined such that the probability of accepting a system whose maintainability falls belong a specified value.